Modelo estratégico para la inclusión del Tetra Pak - Cárdenas Jarava, Javier Ignacio (Universidad Antonio Nariño, 2022)
Within the activities established in the internship as a member of the RE project (Recycle, Design, and Use), the deliverable as an industrial designer is to present a strategic model for the recovery of Treta Pak, from design management to contribute to the collection, recovery and treatment. The volumes of waste from Tetra Pak are generating an impact on the environment which must be taken into account within the local reuse production chain. The actions and behaviors of the social actors are considered, as a variable that articulates the quantity, quality, and treatment of the Tetra Pak material, allowing, in turn, to determine and predict the variables that result in the development of the life cycle of the product. aseptic packaging.